2013
DOI: 10.5897/ajpp2013.3465
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of ginger (Zingiber officinale Roscoe) against lead acetate-induced hepatotoxicity in rats

Abstract: Humans are exposed to a number of toxic elements in the environment. Lead, widely used in industry, is a great environmental health problem of both humans and animals. Effects of reactive oxygen species (ROS) generation have been postulated to be major contributors to lead-exposure related disease. Effects of aqueous solution of whole ginger on hepatic injury due to lead-induced oxidative stress in experimental rats have been investigated. Lead acetate (LA) at a dose of 500 ppm in drinking water was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Treatments with lead acetate were found to cause a significant increases in serum ALT, AST and ALP activities [51 &52]. Attia et al [53] reported increased activities of ALT and AST in rats during lead poisoning. Increasing levels of AST and ALT in the plasma of treated rats is mainly due to the leakage of these enzymes from the liver cytosol into the blood stream [54].…”
Section: Discussionmentioning
confidence: 99%
“…Treatments with lead acetate were found to cause a significant increases in serum ALT, AST and ALP activities [51 &52]. Attia et al [53] reported increased activities of ALT and AST in rats during lead poisoning. Increasing levels of AST and ALT in the plasma of treated rats is mainly due to the leakage of these enzymes from the liver cytosol into the blood stream [54].…”
Section: Discussionmentioning
confidence: 99%
“…The results show data from 3 experiments, with ratios given as means ± SEM. paraben [Asnani and Verma, 2009], lead [Attia et al, 2013], alcohol [Shanmugam et al, 2010], and arsenite [Morakinyo et al, 2013]. These effects have been attributed to its antioxidant mechanisms through enhancement of the activity of the antioxidant enzymes (SOD, GPx, and CAT) and the content of nonenzymatic (glutathione and ascorbic acid) antioxidants.…”
Section: Ginger ( Z Officinalementioning
confidence: 99%
“…Fluoride exposure would induce both pathomorphological and metabolic changes in the liver. [20] In this study,it is seen that administration of fluoride to rats caused a significant increase in the level of lipid peroxidation as indicated by the significant increase in MDA. Our results also corroborate well with that of Shivarajashankara et al [21] who demonstrated that 100 ppm of fluoride increases the rate of lipid peroxidation in liver.…”
Section: Haematological Parametersmentioning
confidence: 85%